Distribution of colonization factor antigens among enterotoxigenic Escherichia coli strains isolated from patients with diarrhea in Nepal, Indonesia, Peru, and Thailand. - Nirdnoy, W (1997)
Samples (1,318) of enterotoxigenic Escherichia coli (ETEC) isolated in 1994-1995 from children with diarrhea from Nepal, Indonesia, Peru, and Thailand were examined for colonization factor antigen (CFA) and coli surface (CS) antigens. Fifty-five percent of 361 heat-labile and heat-stable (LT-ST), 14% of 620 LT-only, and 48% of 337 ST-only ETEC had CFA/CS antigens. LT-ST ETEC strains were predominantly in the CFA II group, and ST only strains were in the CFA IV group. Additional studies are needed to identify ETEC strains that do not have CFA/CS antigens.